Harnessing Seed Endophytic Microbiomes: A Hidden Treasure for Enhancing Sustainable Agriculture - Ayomide Emmanuel Fadiji; Adedayo Ayodeji Lanrewaju; Iyabo Olunike Omomowo; Fannie Isela Parra-Cota; Sergio de los Santos-Villalobos (Plants)
Microbes perform diverse and vital functions in animals, plants, and humans, and among them, plant-associated microbiomes, especially endophytes, have attracted growing scientific interest in recent years. Numerous plant species thriving in diverse environments have been shown to host endophytic microbes. While endophytic bacteria commonly colonize plant tissues such as stems, roots, and leaves, seed-associated endophytes generally exhibit lower diversity compared to those in other plant compartments. Nevertheless, seed-borne microbes are of particular importance, as they represent the initial microbial inoculum that influences a plant’s critical early developmental stages. The seed endophytic microbiome is of particular interest due to its potential for vertical transmission and its capacity to produce a broad array of phytohormones, enzymes, antimicrobial compounds, and other secondary metabolites. Collectively, these functions contribute to enhanced plant biomass and yield, especially under abiotic and biotic stress conditions. Despite their multifaceted roles, seed microbiomes remain underexplored in plant ecology, and their potential benefits are not yet fully understood. This review highlights recent advances in our understanding of the diversity, community composition, mechanisms of action, and agricultural significance of seed endophytic microbes. Furthermore, it synthesizes current insights into how seed endophytes promote plant health and productivity and proposes future research directions to fully harness their potential in sustainable agriculture.